The Correlation Between Students' Vocabulary Mastery and Their Reading Comprehension in Recount Text at MTs Yayasan Misi Islamiyah PT. Inecda Indragiri Hulu - Yulfischa, Elda; Raudhatul Miski, Cut (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
Elda Yulfischa (2023): The Correlation between Students Vocabulary Mastery and Their Reading Comprehension in Recount Text at MTs Yayasan Misi Islamiyah PT. Inecda Indragiri HuluThe purpose of this research is to describe the correlation between students vocabulary mastery and their reading comprehension in recount text at MTs Yayasan Misi Islamiyah PT. Inecda Indragiri Hulu. This research was descriptive quantitative. There were 35 students as samples chosen by using total sampling technique. In collecting the data, the researcher distributed the test to the respondents to determine the students vocabulary mastery, which consisted of 20 item statements that was constructed based on the indicators of vocabulary mastery and to know the reading comprehension in recount text, the researcher distributed the test. The researcher used descriptive statistics to analyze the data. The outcome of this research showed that r observed was 0.495. With degree of significance 1%, the score of r table obtained was 0,282, therefore, robserved>rtable (0.495> 0.282); meanwhile, with degree of significance 5%, the score of rtable obtained was 0.333, therefore, robserved>rtable (0.495 > 0.282); the outcome of this research showed that the score was significantly correlation between students’ vocabulary mastery and their reading comprehension in recount text at MTs Yayasan Misi Islamiyah PT. Inecda Indragiri Hulu.